2022
DOI: 10.3389/fonc.2022.925671
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmacokinetics of Boronophenylalanine and Its Uptakes in Gastric Cancer

Abstract: Boron neutron capture therapy (BNCT), a cellular-level particle radiation therapy, combines boron compounds selectively delivered to tumor tissue with neutron irradiation. Boronophenylalanine (BPA) is a boron compound widely used in malignant melanoma, malignant brain tumors, and recurrent head and neck cancer. However, neither basic nor clinical research was reported for the treatment of gastric cancer using BPA. Selective distribution of boron in tumors rather than that in blood or normal tissue prior to neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Boron and its metabolites are excreted primarily by the urinary system, which explains the high concentrations of boron in the kidneys (Tang et al, 2022). Horn et al (1997) revealed that a single infusion of sodium borocaptate can induce some alterations in the function of a normal kidney, resulting in a reduction of the filtration fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Boron and its metabolites are excreted primarily by the urinary system, which explains the high concentrations of boron in the kidneys (Tang et al, 2022). Horn et al (1997) revealed that a single infusion of sodium borocaptate can induce some alterations in the function of a normal kidney, resulting in a reduction of the filtration fraction.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of boron in different tissues (heart, liver, lung, stomach, and small intestine) of rats revealed a similar pattern in blood except for that in the brain, kidney, and bladder; also noted is that BPA is preferentially distributed in tumor tissue rather than in blood or normal tissues. Although the mechanism for this distribution is unclear …”
Section: Pharmacokinetics Of Some Boron-containing Compoundsmentioning
confidence: 99%
“…Although the mechanism for this distribution is unclear. 688 Other facts in BCC-distribution are not elucidated; as an example, not all boronic acids with a good volume of distribution can reach the whole organism. Thus, bortezomib, an dipeptide boronic acid, has wide distribution but limited access to the central nervous system.…”
Section: Boric and Boronic Acidsmentioning
confidence: 99%